Singapore’s smart city : securing it from emerging cyber threats - Mylrea, Michael (2015)
As Singapore and other smart cities become increasingly connected to the cyberspace so too does their risk of cyber threats. Smart cities need to develop a cyber-smart workforce, technology, policies and new risk management solutions.